Jesus Began to Preach : The Mystery of God's Word - Cantalamessa, Raniero (Book collections on Project MUSE., 2010)
In this volume, a thoroughly revised and expanded version of The Mystery of God's Word, Father Raniero Cantalamessa engages the profound idea of the Eternal Word that becomes Life. The main and constant focus of the book is to show how the word of God illuminates and engages our existence. Cantalamessa uses the words of Scripture, particularly those of Jesus, to reflect on the meaning of a God who speaks, a God who is in relationship with humanity. By encountering these words in prayer and liturgy, we are invited to allow them into our minds and hearts that we may be bearers of the word of God in the world. --Book Jacket.